Manganese and Iron Complexes with H-heterocyclic Carbene Ligands: Synthesis and Catalysis - Pinto, M. F. (2020)
"This thesis describes the synthesis of new manganese and iron complexes bearing N-heterocyclic carbene (NHC) ligands and their application in catalysis. In particular, we have explored the catalytic activity of the new metal complexes in the oxidation of alcohols and in the reduction of carbonyl groups.(...)"